(untitled) (Jóvenes en la Ciencia, 2025)
engagement within academic institutions. This paper describes the development, customization, and deployment of a Question and Answer (Q&A) forum based on the Askbot platform, hosted on PythonAnywhere. The primary objective of this project is to establish a respectful online space where all members of the University of Guanajuato community—including professors, administrators, and students— could interact, express suggestions, and propose ideas for the university. We focused on identifying the underlying programming languages of Askbot, revealing its reliance on Python, JavaScript, Django, and Jinja2. Preliminary tests were conducted on local servers to understand Askbot’s functionality and explore customization avenues. A key focus was the integration with MySQL for robust database management and data extraction for administrative analysis. The selection of PythonAnywhere as the web hosting solution followed a comparative analysis through different options. The deployment process involved resolving various installation challenges via the PythonAnywhere bash environment. Customization efforts included designing a unique forum logo, a default user logo, and adapting the website’s color scheme to reflect the University of Guanajuato’s institutional colors. The forum was successfully tested by university students, where participants were invited to submit suggestions and comments. Furthermore, an initial exploration into sentiment analysis of forum comments, using Textblob, a Python-based library, yielded accurate insights into user sentiment. This work demonstrates the feasibility and benefits of creating dedicated digital platforms to enhance internal university communication and facilitate feedback collection.